Pelaksanaan Kurikulum Dipelajari oleh Pelajar Pendidikan Islam di Kolej Pengajian Islam Selatan Thailand - Binhassan, Abdulrasyid; Salae, Mahsdi; Syarif Hayisama-ae, Muhammad; Chapakia, Fathiyah (Journal of Information System and Education Development, 2023)
This study aims to examine how the implementation of curriculum in Islamic studies colleges, public universities in the South of Thailand. A curriculum audit was adapted to explain the curriculum studied. The design of this study uses a qualitative case study method involving as many as nine students from an Islamic studies college in the south of Thailand selected as study participants. The main criterion for the selection of the study participants was that the students were following the subject of Islamic education based on the informants' information. The method of data retrieval is made by interview, observation and document analysis, the data which is "emergent" and "naturalistic" in nature is filtered and analyzed through the process of coding and sub-coding which forms themes and sub-themes to answer the questions of the study. The study findings show the implementation of the curriculum learned through textbooks whose content is important and useful, easy, and appropriate, adds new information, achieves goals and objectives, follows the plan and quality standards of the curriculum and this can help students achieve the objectives. For the implementation of the curriculum studied for teachers who show the attitudes, methods, and activities of teachers, they have their own style, firm, cheerful, clear voice and use of simple language, as for the activity is through the group in the form of discussion and presentation. For the implementation of the curriculum learned for students shows they have the experience of educational backgrounds